Color transfer between images - Luo, Huiyi (Nanyang Technological University, 2023)
Digital image processing has become a ubiquitous technology in contemporary times, and one of the most performed operations is changing the colour of an image. Colour transfer is a method that replaces the dominant colour scheme of a source image with the colour characteristics of a target image, while the scene of the source image remains unchanged. This technique is also applicable to videos, such as transferring an old black-and-white film into a colour film. As a result, colour transfer's effectiveness and performance have come under scrutiny. The present report analyses and evaluates two different algorithms from previous studies, namely "Colour Transfer Between Images" and "N-Dimensional Probability Density Function Transfer and its Application to Colour Transfer." Furthermore, the report will compare the performance and efficiency of both algorithms using colour histogram and colour cloud.